Aplikasi Web Service Perbankan untuk Pembayaran Formulir Pendaftaran Mahasiswa Baru - Puspaningtyas Sanjoyo Adi (Media Teknika, 2017)
The new student registration process begins with the process of filling out the registration form where to get it, the prospective student pays to get the form. Sanata Dharma University cooperates with the bank to develop an application to pay registration form with web service technology. The advantage of this technology is electronic service and can work 24 hours. Web service technology is a service that allows communication between machines performed through a computer network with HTTP protocol web server. The web service application was developed and implemented by Sanata Dharma University and CIMB Niaga bank in October 2017. From the observation of January 2018 compared to January 2017, the January 2018 transaction increased by about 12% compared to January 2017. The proportion of web service transactions is around 30% of total transactions where 80% of them are conducted outside office hours. This data indicates that the knowledge of electronics services of prospective students and their parents is good enough.Keywords: web service, registration form, new students